Diagnostic accuracy of 16S rDNA PCR, multiplex PCR and metagenomic next-generation sequencing in periprosthetic joint infections: a systematic review and meta-analysis - Olearo, Flaminia; Zein, Said El; Portillo, Maria Eugenia; Zapf, Antonia; Rohde, Holger; Berbari, Elie F; Wouthuyzen-Bakker, Marjan (Clinical microbiology and infection, 2025)
The diagnostic accuracy of 16S rDNA PCR, multiplex PCR (mPCR), and metagenomic next-generation sequencing (mNGS) in periprosthetic joint infections (PJIs) remains unclear. This study aims to evaluate the diagnostic accuracy of 16S rDNA PCR, mPCR, and mNGS in PJI. Data sources: Data sources included PubMed and Embase (January 1, 2000-March 1, 2024), with no language restrictions. Studies containing sufficient data to construct a 2 × 2 contingency table allowing for sensitivity and specificity calculation were considered. Participants included adults (≥18 years) with PJI and appropriate control groups. Tests included 16S rDNA PCR, mPCR, and mNGS. Diagnosis required adherence to Musculoskeletal Infection Society, Infectious Diseases Society of America, International Consensus Meeting, European Bone and Joint Infection Society criteria. Studies employing alternative author-defined criteria were included only if they did not rely solely on positive cultures to define PJI. Quality Assessment of Diagnostic Accuracy Studies 2 was used. A bivariate model calculated pooled diagnostic odds ratios (DORs), sensitivities, and specificities, each with 95% CIs. Seventy-nine studies were included, comprising 3940 PJI cases and 4700 uninfected controls. Pooled sensitivity/specificity were 80.0% (95% CI, 75.4-84.3%)/94.0% (95% CI, 91-96%) for 16S rDNA PCR; 62.2% (52.5-70.9%)/96.2% (93.2-97.9%) for mPCR; and 88.6% (83.3-92.4%)/93.2% (89.5-95.6%) for mNGS. Notably, mNGS had the highest DOR (105.9; 95% CI, 60-186.9). A sensitivity analysis excluding lower-quality studies resulted in increased DORs for all methods. These molecular techniques display strong diagnostic accuracy for identifying PJI. Although mNGS yielded the highest DOR, numerous technical and practical challenges preclude its routine use for PJI diagnosis. Significant heterogeneity across studies warrants cautious interpretation and underscores the need for future comparative research.